An operational direct model to accurately determine crop evapotranspiration of crops cultivated in the Mediterranean region - Rana G.; Katerji N.; Ferrara R.M. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
Two methods can be considered as able to determine E for well irrigated crops. The first method is indirect (the 'crop coefficient approach'). It is based on the knowledge of a crop coefficient, Kc, and an estimation of the reference evapotranspiration of grass E0 . The second method directly calculates the E of a crop, without a step through a reference surface. It similarly applies a Penman-Monteith type formula. However, in this method the canopy resistance, rc, is specific for each species, it is not constant but variable as a function of climatic characteristics of the atmosphere below the top of the boundary layer above the crop. This study proposes to explore and to test a more operational version of the direct model. In this version, the canopy resistance rc will be considered as constant but specific for each crop. The performances of this method are evaluated with respect to the above cited direct and indirect methods, by means of experimental validation carried out on 3 crops having contrasted height. The best performance was given by the original version of the direct model, both at daily and hourly scales. The operational version of the direct model gave acceptable results only for grass. The indirect model gave the worst results both at daily and hourly scales. The practical use of this new version is discussed in the conclusions.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)